201 Clinical presentation profiles and natural history of cardiac amyloidosis: long-term monocentric analysis (1990–2020). (8th December 2021) - Porcari, Aldostefano; Allegro, Valentina; Pagura, Linda; Longo, Francesca; Rossi, Maddalena; Varra, Guerino Giuseppe; Dore, Franca; Bussani, Rossana; Merlo, Marco; Sinagra, Gianfranco
Abstract: Aims: Cardiac Amyloidosis (CA) is considered a rare condition comprising different entities. Epidemiological data are limited and the natural history of disease is largely unknown. Understanding the clinical profiles at presentation, the impact of novel diagnostic strategies and the prognostic predictors at baseline will improve patients' clinical management. We aimed to examine the epidemiology and natural history of CA in the last 30 years at a tertiary referral centre for amyloidosis. Methods and results: Data of patients included in the prospective 'Cardiac Amyloidosis Registry' of Trieste from January 1990 to December 2020 were extracted from an electronical database and analysed. The diagnosis of CA was made in presence of (a) amyloid deposition found at endomyocardial biopsy (EMB), or (b) high grade cardiac uptake at bisphosphonate scintigraphy in absence of monoclonal components. Cardiological data of patients included (i) clinical examination, (ii) electrocardiogram (ECG), (iii) echocardiography and (iv) medications. The primary outcome measure was all-cause mortality. The secondary outcome measure was cardiac death. Of the 143 patients with CA included in this analysis, 77 (54%) were diagnosed before 2016 (historical cohort) and 66 (46%) ≥2016 (contemporary cohort). Light chain (AL) amyloidosis and transthyretin (ATTR) amyloidosis accounted for 49% and 38%, respectively, of all CA patients. CA of unknown aetiology accounted for 13% of cases. CA was diagnosed by EMB in 98 (69%) patients and by cardiac scintigraphy with bone tracers in 45 (31%) patients. Patients in the contemporary cohort (67% ATTR-CA) were diagnosed more frequently by non-invasive approach compared to those in the historical cohort. At a median global Follow-up of 36 months, a more favourable outcome was found in a) patients from the contemporary cohort compared to those from the historical cohort ( P < 0.001), b) ATTR- compared to AL-CA (at 18 months of Follow-up 42 (85%) ATTR patients and 32 (60%) AAL patients were alive, P = 0.013), and, (c) patients diagnosed non-invasively by scintigraphy rather than by histology (at 18 months of Follow-up 36 (80%) of patients diagnosed by cardiac scintigraphy and 57 (60%) of those diagnosed by histology were alive, P = 0.001). Of note, while no difference in outcome was found among AL- and ATTR-CA in the historical cohort, ATTR-CA patients had lower all-cause mortality and cardiac death than AL-CA patients in the contemporary cohort. Overall, death for end stage HF was more prevalent in patients with AL- than ATTR-CA (58% vs. 25%, P = 0.002). At univariable analysis, ACE-i and beta blockers (BBs) therapy were associated with a more favorable outcome [HR: 0.38, (0.26–0.60, P < 0.001) and HR: 0.53 (0.33–0.85, P = 0.008), respectively], while experiencing a previous syncope and having low QRS voltages at surface ECG portended a worse overall survival [HR: 2.42 (1.3–4.5, P = 0.006) and HR: 1.94 (1.3–3.0, P = 0.002), respectively]. At multivariate analysis, treatment with ACE-i, BBs, and syncope had independent prognostic value [HR 0.41 (0.23–0.71, P = 0.002); HR 0.50 (0.31–0.82, P = 0.007), and HR: 2.1 (1.0–4.1, P = 0.040); respectively]. Conclusions: The epidemiology and natural history of CA has been changing. Over years, ATTR-CA had the most favourable outcome. NYHA functional class, syncope, BBs and ACE-i therapy were useful parameters for prognostic stratification. Further research is needed to investigate if they could be integrated in multiparametric scores for more accurate outcome prediction.